Brand rewired connecting intellectual property, branding and creativity strategy - Chasser, Anne H. (Wiley, 2010)
""How do Procter & Gamble and Google and companies like them build a billion-dollar brand? They design strong intellectual property strategy into their innovation and branding processes through the power of collaboration and interdisciplinary teams. Whether a company is maintaining a brand that has endured for more than 100 years, such as Tide, or creating a new brand that will capture the attention of the world, such as Google, a rewired branding process can provide key competitive advantages."--Chapter 1 of Brand Rewired" "Consider this: it's generally accepted that to achieve an increase in margin, market share, revenue, and market value, a company must innovate and create for consumer needs and wants. But renowned IP strategists Anne Chasser and Jennifer Wolfe argue in Brand Rewired that in the future---i.e., now---companies must add another layer of thinking to the creative process: an interdisciplinary approach that considers long-lasting intellectual property from the start of the creative process." "If the brand process is approached this way, you will get the job done faster, utilize fewer resources, reduce costs, and increase the likelihood of success. Intelligent and timely, this book takes a look at:" "Featuring surprisingly revealing interviews with executives from leading worldwide companies including Procter & Gamble, Kodak, Yahoo!, Kraft Foods, Kimberly-Clark, Harley-Davidson, General Mills, LPK, JWT, Scripps Networks Interactive, Northlich, and more, this book is not just another IP strategy guide. This is the strategic direction every brand manager, marketing professional, intellectual property lawyer, valuation professional, intellectual asset manager, in-trapreneur, or entrepreneur needs to gain a step on the competition." "Want to see our economy make a sustainable recovery from its current financial crisis? Want your business to survive in this century? Get Brand Rewired."--Jacket.